Advanced automotive thermal management – Nonlinear radiator fan matrix control. (August 2015) - Wang, Tianwei (Thomas); Wagner, John
Abstract: Advanced automotive cooling systems for gasoline and diesel engines can improve the powertrain performance. The replacement of the mechanical driven coolant pump and radiator fans with computer controlled servo-motor actuators, and update of the wax-based thermostat valve with a 3-way variable position smart valve, allow the coolant flow rate and proportion directed through the radiator to be carefully adjusted. A smart thermal management system approach can regulate the forced convection heat transfer process to match the engine׳s cooling needs. This paper presents a Lyapunov based nonlinear control strategy to solely operate the radiator fan matrix for transient engine temperature tracking. A reduced order mathematical model serves as the basis for the closed-loop feedback system. An adaptive backstepping method was implemented to derive the control law. An experimental test bench with multiple radiator fans, heat exchanger, wind tunnel, coolant pump, three way valve, and engine thermal load has been fabricated. Representative numerical and experimental tests demonstrate that the advanced control strategy can regulate the engine temperature tracking error within 0.12 °C and compensate the unknown heat load. The nonlinear controller provided superior performance in terms of power consumption and temperature tracking as evident by the reduced magnitude when compared to a classical PI with lookup table based controller and a bang bang controller.